PERAN LPTK DALAM MEMPERSIAPKAN GURU YANG KOMPETEN - Rohman, Abdul (At-Taqaddum, 2013)
The quality of education is influenced by some factors, i.e.: educator (teacher), student, curriculum, environment, etc; but in the school context, teacher is the school. It is because a well-written curriculum is not automatically succeded in actual curriculum. In the case of curriculum implementation, it is highly depended on the teacher. A qualified and commited teacher is pre-requisite for successfully implementing a curriculum. Shortly, it is said that giving deep attention for the teacher is necessity for producing a qualified education. Consequently, well handling an institution (LPTK) that yields teachers have to be done in the sake for improving the quality of education, LPTK should continuously innovate and improve themselves for outcoming the best teacher, and in the turn for progress of the education it self.